ENT 530 Social Media Portfolio: Chocodap's / Nurul Syafiqah Kholil - Kholil, Nurul Syafiqah (2021)
Chocodap’s is one of the products under FS Mega World Sdn Bhd that is located in Selangor. The founder of this product is May Sarah Nadiah binti Meor Mohamad and CEO of Chocodap’s is her husband, Mohd Farhan bin Mohamad Zainuddin. This business has been managed by them for 5 years. Chocodap’s offer many types of chocolates with different flavours which are hard to find in the market. The difference between this product and others is it is made from premium chocolates and tastes like international chocolates brands although it is a local brand. Moreover, these products also have agents from many places and different states which are focused on all people in Malaysia. To fulfill a media social portfolio assignment, I decided to become a dropship of this product since I also like to eat chocolates. I am sure that this product will be accepted by many customers from different groups because of the affordable price and the good taste of the chocolates. Although nowadays there are many types of famous chocolate such as Cadburry Dairy Milk, Ferrero Rocher, Hershey and Beryl’s, it is one of the challenges that this business needs to face in order to become as famous as other products. Other than that, as a dropship I have created and managed a Facebook page for Chocodap’s in the marketing and promotional activities. In order to become a successful dropship, I need to be consistent and patient in marketing the products. Moreover, knowledge is also one of the important things to grow the business.